Caffeine Consumption Habits of New Zealand Tertiary Students - Stachyshyn, Saskia (Nutrients, 2021)
Adverse effects associated with excessive caffeine consumption combined with increasing numbers and availability of caffeine-containing products are causes for concern. Tertiary students may be at increased risk of consuming excessive amounts of caffeine due to seeking caffeinated products with well-known wakefulness effects and cognitive benefits. This study explored caffeine consumption habits of New Zealand tertiary students (317; ≥16-years) using a previously validated caffeine consumption habits (CaffCo) questionnaire. Most (99.1%) regularly consumed caffeinated products, especially chocolate, coffee and tea, with coffee, tea and energy drinks contributing most to total caffeine intake. Median estimated caffeine intake was 146.73 mg·day(−1), or 2.25 mg·kgbw(−1)·day(−1). Maximum and minimum intakes were 1988.14 mg·day(−1) (23.51 mg·kgbw(−1)·day(−1)) and 0.07 mg·day(−1) (0.02 mg·kgbw(−1)·day(−1)), respectively. One-third (34.4%) of caffeine consumers ingested caffeine above the adverse effect level (3 mg·kgbw(−1)·day(−1)) and 14.3% above the safe limit (400 mg·day(−1)). Most caffeine consumers (84.7%), reported experiencing at least one ‘adverse symptom’ post-caffeine consumption, of which 25.7% reported effects leading to distress or negatively impacting their life. Experiencing ‘adverse symptoms’ did not, however, curtail consumption in the majority of symptomatic participants (~77%). Public health initiatives directed at tertiary students may be important to reduce potential caffeine-related harm.